Applying the Kuhn–Tucker model to estimate the value of recreational ecosystem services in Sicily. Issue 7 (2nd July 2016) - Nicita, Lea; Signorello, Giovanni; De Salvo, Maria
Abstract : This paper applies the Kuhn–Tucker model to estimate recreation demand of parks in Sicily. We estimate a fixed coefficient specification and a random coefficient specification to take into account heterogeneity across visitors. Estimates suggest a diversity of preferences across the population and that parks with higher level of quality attributes are more likely to be visited. We also simulate two sets of hypothetical policy scenarios to evaluate and compare the recreational value of each park and the welfare impacts of changes in a quality attribute.